Lebensqualität und Zufriedenheit während der Teilnahme am Diabetes-Präventionsprogramm GLICEMIA: eine cluster-randomisierte, kontrollierte Studie - Schmiedel, Karin; Mayr, Andreas; Fießler, Cornelia; Schlager, Helmut; Friedland, Kristina (Gesundheitswesen, 2020)
OBJECTIVES: We aimed to assess the health-related quality of life as well as participant satisfaction during the pharmacy-based diabetes prevention program GLICEMIA. METHODS: GLICEMIA comprises 3 individual counseling sessions and 5 group-based lectures addressing a lifestyle modification. In a cluster-randomized controlled trial, GLICEMIA was compared with reduced standard information in the control group. After 12 months, the groups were compared regarding the diabetes risk score FINDRISC, health-related quality of life with the 12-item Short Form health survey (SF-12) and participant satisfaction. RESULTS: In total, the data of 1,087 participants were analyzed. During GLICEMIA, 38.9% reduced their FINDRISC whereas 20.9% reached this goal in the control group. Moreover, the physical quality of life improved significantly in the intervention group compared with the control group (adjusted effect size: 2.39 points, 95% CI 1.43-3.34). Participants of GLICEMIA who reduced their diabetes risk had enhanced mental and physical quality of life after one year. This was not observed in the control group. The overall benefit and satisfaction were rated very high in the intervention group. CONCLUSION: Participation in GLICEMIA results in a significant reduction of the diabetes risk according to the FINDRISC, as well as an improved physical and mental quality of life. The high satisfaction of the participants reflects the overall benefit. Nationwide implementation of the program is recommended.
CRIS-Team Scopus Importer:2020-11-27